플라즈마 처리에 의한 폴리비닐리덴플로라이드 나노섬유의 젖음성 - 이승훈; 장선호; 소윤미; 이헌수; 양철민; 윤중현; 김찬 (한국섬유공학회, 2018)
Poly(vinylidene fluoride) (PVDF) is a critical polymeric material used in the mass production and application of electrospun nanofibers, and is popular due to its excellent properties. However, electrospun PVDF nanofibers are very hydrophobic and possess low surface energies, limiting their broad application. In this work, we investigated practical methods for the hydrophobic surface modification of PVDF nanofibers using four techniques: radio-frequency (RF) and PIN-type atmospheric plasmas, planar inductively coupled plasma (ICP), and planar capacitively coupled plasma (CCP). The use of RF atmospheric plasma was ineffective under the experimental conditions used, while the PIN-type atmospheric plasma efficiently modified PVDF nanofiber surfaces locally. The application of planar CCP to PVDF nanofibers was more effective than planar ICP for the same experimental conditions. In particular, the water contact angles of samples treated with planar CCP for 600 s and 900 s were 25 ° and 10 ° respectively, and wettability improved. Analysis with FTIR, XPS, and FE-SEM showed that the surface CF and CH hydrophobic groups were destroyed without damaging the PVDF nanofibers, and hydrophilic species such as C=O, OH, and COOH were formed. As a consequence, quantitative analysis of nanofiber chemical composition is necessary when treated by plasmas, providing insight into the correlation of specific property changes with processing conditions, and indicating precise research results and application examples.